Barakah, Falāḥ, and Iḥsāniyyah Rationality: Spiritual Entrepreneurship Among Muslim MSME Entrepreneurs in Tana Luwu, Indonesia - Muhammad Alwi; Agung Zulkarnain; Iftidal Gunawan (Program Studi Ekonomi Syariah, FEBI UIN Datokarama Palu, 2026)
This study examines spiritual entrepreneurship among Muslim MSME entrepreneurs in Tana Luwu, Indonesia, by analyzing how barakah, falāḥ, and iḥsāniyyah rationality shape everyday economic practices. It addresses a gap in Islamic entrepreneurship studies, which remain largely normative and centered on formal urban business settings, leaving local religious community-based MSMEs underexplored. Using a descriptive qualitative design within an interpretive paradigm, data were collected through in-depth interviews, field observations, and documentation involving 20 Muslim MSME entrepreneurs selected through purposive sampling. Data were analyzed through reduction, presentation, and conclusion drawing, with credibility strengthened through source and methodological triangulation. The findings show that niyyah, amānah, iḥsān, tawakkul, and barakah orientation are embedded in business practices, shaping honesty, halal commitment, trust-based relationships, and resilience amid economic uncertainty. Business success is understood not merely as profit accumulation but as falāḥ-oriented well-being encompassing material, social, moral, and spiritual dimensions. The study introduces iḥsāniyyah rationality as an alternative model of economic rationality and offers a conceptual basis for value-based MSME development and social sustainability within local Muslim economic communities.